જો ${x_1},{x_2} \in [ - 1,\,1]$ માટે $f({x_1}) - f({x_2}) = f\left( {\frac{{{x_1} - {x_2}}}{{1 - {x_1}{x_2}}}} \right)$, તો $f(x) =$
$\log \frac{{(1 - x)}}{{(1 + x)}}$
${\tan ^{ - 1}}\frac{{(1 - x)}}{{(1 + x)}}$
$\log \frac{{(1 + x)}}{{(1 - x)}}$
ઉપર ના બધા
વિધેય $f(x) = \;|px - q|\; + r|x|,\;x \in ( - \infty ,\;\infty )$, કે જ્યાં $p > 0,\;q > 0,\;r > 0$ ની ન્યૂનતમ કિમંત ધારો કે માત્ર એકજ બિંદુએ મળે જો . . .
જો ${e^x} = y + \sqrt {1 + {y^2}} $, તો $y =$
અહી $f(x)=x^6-2 x^3+x^3+x^2-x-1$ અને $g(x)=x^4-x^3-x^2-1$ બે બહુપદી છે. અહી $a, b, c$ અને $d$ એ $g(x)=0$ ના બીજ હોય તો $f(a)+f(b)+f(c)+f(d)$ ની કિમંત મેળવો.
વિધેય $f(x) = \frac{{\sqrt {1 - {x^2}} }}{{1 + \left| x \right|}}$ નો વિસ્તાર ......... છે.
દરેક $x\,\, \in \,R\,,x\, \ne \,0,$ જો ${f_0}(x) = \frac{1}{{1 - x}}$ અને ${f_{n + 1}}(x) = {f_0}({f_n}(x)),$ $n\, = 0,1,2,....$ તો ${f_{100}}(3) + {f_1}\left( {\frac{2}{3}} \right) + {f_2}\left( {\frac{3}{2}} \right)$ ની કિમંત મેળવો.